Progress in Advanced Computing and Intelligent Engineering Proceedings of ICACIE 2017, Volume 2 - Panigrahi, Chhabi Rani; Pujari, Arun K.; Misra, Sudip; Pati, Bibudhendu; Li, Kuan-Ching (Advances in Intelligent Systems and Computing, 2019)
This book features high-quality research papers presented at the International Conference on Advanced Computing and Intelligent Engineering (ICACIE 2017). It includes sections describing technical advances in the fields of advanced computing and intelligent engineering, which are based on the presented articles. Intended for postgraduate students and researchers working in the discipline of computer science and engineering, the proceedings also appeal to researchers in the domain of electronics as it covers hardware technologies and future communication technologies.